Resource-use plasticity governs the causal relationship between traits and community structure in model microbial communities - Brendon McGuinness; Stephanie C. Weber; Frederic Guichard (Proceedings of the National Academy of Sciences, 2025)
Resolving the relationship between species’ traits and their relative abundance is a central challenge in ecology. Current hypotheses assume relative abundances either result from or are independent of traits. However, despite some success, these hypotheses do not integrate the feedback interactions between traits and abundances to predictions of community structure such as relative abundance distributions and trait–abundance relationships. Here, we study how plasticity in resource-use traits governs the causal relationship between traits and relative abundances. We adopt a consumer–resource model that incorporates resource-use plasticity that operates to optimize organism growth, underpinned by investment constraints in physiological machinery for the acquisition of resources. We first show how plasticity in a single species in a community allows all other nonplastic species to coexist, a case of facilitation emerging from competitive interactions. Here, resource-use optimization by the plastic species results in a trade-off between minimizing its similarity with competitors while maximizing its resource-use efficiency in its environment. We apply this trade-off to predict trait–abundance relationships and reveal, unexpectedly, that initial traits are better predictors of equilibrium abundances than equilibrium traits. We then demonstrate that the rate of plasticity controls the coupling strength between trait and abundance dynamics, predicting species’ equilibrium relative abundances. This result highlights the importance of transient dynamics in driving species sorting despite the emergence of “ecological equivalence” at equilibrium. Thus, our study explains the unexpected co-occurrence at equilibrium of emergent neutrality and strong trait–abundance relationships. We propose trait–abundance feedback as an ecoevolutionary mechanism linking community structure and assembly, highlighting trait plasticity’s role in driving community dynamics.